Penentuan Hari Baik Pernikahan Masyarakat Desa Bandar Khalifah Menurut Pandangan Islam - Nasution, Erwinsyah; Abrar M Dawud Faza (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The purpose of this research is to recognize how to determine the good day of marriage for Bandar Khalifah villagers and to find out how the Islamic perspective on the customs of determining the good day of marriage for Bandar Khalifah villagers. This research is field research (field research), and is descriptive analytic in nature, namely research that describes and explains the information obtained from the field, then analyzes it. This research uses information collection techniques of monitoring or observation, question and answer, and archiving. On the other hand, the analysis is a qualitative analysis with a deductive thinking approach. Based on the research results of determining the good day of marriage for Bandar Khalifah villagers, marriage can be tried in the months of Ba'da Mulud, Jumadil Akhir, Rajab, Ruwah and Hari Raya, after that finding the good day of marriage with wuku. There are 4 wuku that are not allowed to carry out marriage are wuku Rigan, Tambir, Langkir, and Bolo. After the date of marriage is set, the next method is the calculation of the weton between the prospective bride and groom. The relevance of these customs is that there is hesitation in not exploring the customs that have become part of the belief, which is feared to cause undesirable circumstances. In Islamic thought, there is no special text that says about the determination of a good wedding day in the Quran or the words of the Prophet Muhammad, because every day is considered good. Therefore, this kind of custom is not in line with Islamic law because it is feared that it can lead to kufr